ANALYSIS OF TRANSACTION COSTS OF LIQUID PETROLEUM GAS (LPG) 3 KG SUPPLY CHAIN IN YOGYAKARTA CITY - Atika Fatimah (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2019)
Liquified Petroleum Gas (LPG) 3 kg is subsidized fuel circulated by Pertamina Corporation. The objective of this research was to analyze the supply chain, the selling margin among distribution agencies, and the transaction cost in the market supply chain of LPG 3 kg in Yogyakarta. The research used primary data such as interview and observation. The data was analyzed with qualitative descrptive analysis. The result of this research show two LPG 3 kg supply chain in Yogyakarta which are Pertamina – Agent – Base Seller – Retailer – Shop Seller – Cosumer and Pertamina – Agent – Base Seller – Retailer – Small and Medium Enterprises. The highest marketing margin obtained by retailers are Rp. 2942/ gas tube in the first supply chain and second supply chain. The hihgest transaction cost is managerial transaction cost is first supply chain and second supply chain which equals to 62,56 percent and 61,97 percent. Followed by 31,26 percent of market transaction cost in the first supply chain and 31,75 percent in the second supply chain. The lowest transaction costs are 6,13 percent of political transaction cost in the first supply chain and 6,26 percent of political transaction cost in the second supply chain. Therefore, the solution to this problem is a review of the highest retail price for LPG 3 kg in Yogyakarta so it could be relevant for agents who experienced the highest transaction cost.